Ferroptosis: Opportunities and Challenges in Treating Endometrial Cancer - Wu, Jianfa; Zhang, Li; Wu, Suqin; Liu, Zhou (Frontiers in Molecular Biosciences, 2022)
Ferroptosis, a new way of cell death, is involved in many cancers. A growing number of studies have focused on the unique role of ferroptosis on endometrial cancer. In this study, we made a comprehensive review of the relevant articles published to get a deep insight into in the association of ferroptosis with endometrial cancer and to present a summary of the roles of different ferroptosis associated genes. Accordingly, we made an evaluation of the relationships between ferroptosis associated genes and TNM stage, tumor grade, histological type, primary therapy outcome, invasion and recurrence of tumor, accessing the different prognosis molecular typing based on ferroptosis associated genes. Additionally, we presented an introduction of the common drugs which targeted ferroptosis in endometrial cancer. In so doing, we clarified the opportunities and challenges of ferroptosis activator application in treating endometrial cancer with a view to providing a novel approach to the disease.